دراسة تحليلية لتطور الزمن الحقيقي في ميكانيك الكم الإحصائي لنظرية المعايرة الصافية (الغليونات بدون الكواركات) مع منشور الكمون حتى الدرجة السادسة (Latakia University Journal -Basic Sciences Series, 2014)
أخذنا مؤثر الهاملتوني الفعال حتى الدرجة السادسة [12] وهذا المؤثر مكّننا من الانتقال من نظرية المعايرة الصافية مع الزمرة SU(2) إلى دراسة ميكانيك الكم الإحصائي مع الزمرة SU(2) وهذا يعني فيزيائيا" أننا انتقلنا من دراسة عدد لا نهائي من الجسيمات و درجات الحرية (بلازما الكواركات والغليونات) إلى دراسة ثلاثة جسيمات ( غلوبال) أي تسع درجات حرية و بالتحديد تسع هزازات لا توافقية و بعدها قمنا بتطبيق صيغة فغنر[16]على الصيغ المتجانسة المتبقية بعد تكميم الصيغ غير المتجانسة واستنتجنا علاقة تطور الزمن الحقيقي للطاقة المغناطيسية الملونة  وللطاقة الكهربائية الملونة  .We take the effective Hamiltonian operator until the sixth degree[12] and this operator has enabled us to convert from pure gauge theory with group SU(2) into the study of statistical quantum mechanics with the group SU(2) and this mean physically we have converted from the study of an infinite number of particles and of freedom degrees (quarks- gluons-plasma) into study of three particles (Global) that mains nine of freedom degrees and specifically nine anharmonic oscillators and after that we apply Wigner’s mode[16] on homogenous modes remaining after quantization of the inhomogenous modes and we have concluded the relation of real-time evolution of the color magnetic energy  and the color electric energy .